A Thematic Analysis of Strategic Flexibility and Green ‎Management Practices in SMEs Facing Market Disruption - Agustina, Tri Siwi; Putra, Riyan Sisiawan; Saputra, I Gusti Ngurah Widya Hadi; Sari, Annisa Arifka; Judijanto, Loso (International Journal of Accounting and Economics Studies, 2025)
This study examines the relationship between strategic flexibility and green management practices in Small and Medium Enterprises (SMEs) that face market disruptions. The aim is to investigate how SMEs integrate these factors to enhance resilience and competitiveness in volatile ‎markets. Using a qualitative approach, the research involves thematic analysis of secondary data from studies published between 2020 and ‎‎2025. The analysis identifies key patterns in how strategic flexibility and green practices influence SME performance during disruptions. ‎The findings show that SMEs adopting both strategic flexibility and green management practices reported better performance during market ‎disruptions. SMEs that integrated these two practices experienced enhanced resilience, highlighting the importance of combining flexibility ‎and sustainability in navigating market uncertainty. This research contributes to the literature by highlighting the complementary nature of these two factors and provides new insights into how SMEs can effectively leverage both for long-term success. The study underscores the value of ‎integrating strategic flexibility with green management to improve SME resilience. It also suggests that external support mechanisms, such ‎as government incentives, are critical in helping SMEs overcome barriers to adopting these practices. Future research should focus on ‎exploring the challenges SMEs face in implementing these practices, particularly in developing economies, and their long-term effects on ‎business growth‎.
Keywords: Green Management; Market Disruption; SMEs; Strategic Flexibility; Sustainability